Efektivitas Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar IPAS Siswa Kelas IV SD - Mufti, Maisarah; Akhbar, M Taheri; Selegi, Susanti Faipri (STKIP Andi Matappa Pangkep, 2024)
This research aims to determine the effectiveness of the problem based learning model on the science learning outcomes of class IV students at SDIT Annajiyah Lubuklinggau. The research method used is a quantitative method with a Pre Experimental Design research design in the form of One Group Pretest-Posttest. The sample in this study consisted of one class, namely class IV, totaling 20 people. The data collection technique used is a test instrument in the form of multiple choice questions. The data analysis technique uses the t test (paired samples t-test). Based on the research results, the average IPAS pretest score was 50.50, while the average IPAS posttest result was 84.00, resulting in an increase of 33.3. The results of the t-test analysis show that the significance value is 0.000 <0.05. So it can be stated that Ha is accepted and Ho is rejected, so it can be concluded that the use of the problem based learning model is effective on the science learning outcomes of grade IV SD.